2021
DOI: 10.3354/meps13612
|View full text |Cite
|
Sign up to set email alerts
|

Climate alters the migration phenology of coastal marine species

Abstract: Significant shifts in the phenology of life-cycle events have been observed in diverse taxa throughout the global oceans. While the migration phenology of marine fish and invertebrates is expected to be sensitive to climate change, the complex nature of these patterns has made measurement difficult and studies rare. With continuous weekly observations spanning 7 decades in Narragansett Bay, Rhode Island (USA), the University of Rhode Island Graduate School of Oceanography trawl survey provides an unprecedented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 60 publications
1
39
0
Order By: Relevance
“…2013; Langan et al. 2021). Summer temperatures that exceed a species’ thermal tolerance threshold, however, would likely affect the phenological response by causing egress to occur earlier (Neuheimer et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013; Langan et al. 2021). Summer temperatures that exceed a species’ thermal tolerance threshold, however, would likely affect the phenological response by causing egress to occur earlier (Neuheimer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature increases cause changes in the phenology (timing of immigration and emigration) of fishes into and out of estuaries, whereby summer residents generally exhibit earlier ingress and later egress, a global response pattern across taxa (Poloczanska et al 2013;Langan et al 2021). Summer temperatures that exceed a species' thermal tolerance threshold, however, would likely affect the phenological response by causing egress to occur earlier (Neuheimer et al 2011;Thaxton et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There are fewer examples of altered migration phenology and seasonal residence times of warm water fishes, with implications for seasonal species diversity and dominance, but these patterns are increasing (Wood et al 2009; Cohen et al 2018; Staudinger et al 2019). For example, a recent study analyzing a 60‐year historical dataset of Narragansett Bay, Rhode Island, observed changes ranging from weeks to months in the migration phenology of 8 out of 12 fish and squid species, with summer species extending and winter species contracting residence times in the system (Langan et al 2021). Friedland et al (2020) used an ensemble of species distribution and habitat models to evaluate changes in hundreds of fishes and invertebrates across the Northeast continental shelf.…”
Section: What Is the Current State Of Knowledge On How Climate Change Is Modifying Emergent Properties Of Aquatic Ecosystems?mentioning
confidence: 99%
“…There are relatively few modern day examples of aquatic homogenization, unless non‐native invasive species are considered (Scott and Helfman 2001; Villéger et al 2011, 2015; Magurran et al 2015). One exception is the rapid range and phenology expansions of squid populations in coastal areas, including the Humboldt squid Dosidicus gigas in the California Current (Stewart et al 2014), and longfin inshore squid Doryteuthis pealeii in the Gulf of Maine (Mills et al 2013) and Narragansett Bay systems (Langan et al 2021). These short‐lived (i.e., life spans of 1–2 years), and highly opportunistic predators, have taken advantage of warming waters and changes in oxygen minimum zones to expand into habitats and exert biological control on prey in novel habitats (Pershing et al 2019).…”
Section: What Is the Current State Of Knowledge On How Climate Change Is Modifying Emergent Properties Of Aquatic Ecosystems?mentioning
confidence: 99%
“…Climate change has led to well-documented changes in marine, terrestrial and freshwater ecological communities stemming from a diversity of processes, including productivity changes, shifts in species distributions, and changes in timing of seasonal events (phenology) [1][2][3][4][5][6][7][8]. These in turn have the potential to alter competitive and predator-prey interactions, with consequences for species dominance, biodiversity and population persistence.…”
Section: Introductionmentioning
confidence: 99%